Shaping The Protean Career Orientation of Undergraduate Students: Does Academic Advisor Plays Role? - Miftachul Mujib; Nanda Adhi Purusa (Relevance: Journal of Management and Business, 2022)
Undergraduate students who are in pre-employment conditions need to manage their career orientation from an early age. There are still few studies that explore protean career orientation at the pre-employment level (especially at the undergraduate level). This study was aimed to examine the factors that influence the protean career orientation of undergraduate students. It examines the impact of individual adaptability and internal locus of control on protean career orientation, as well as examines the role of academic advisory as a moderator. Data was collected by distributing questionnaires to 160 samples, which were undergraduate students in Indonesia. Data analysis was performed using the SEM-PLS method. There are several research results obtained: 1) individual adaptability has a positive effect on protean career orientation, 2) internal locus of control has a positive effect on protean career orientation, and 3) academic advisory has no moderating effect on both relationships. These results enrich the literature on the antecedents of protean career orientation. There are several implications of these results, including 1) this finding enriches the literature on the study related to the antecedents of protean career orientation, 2) enriches the literature on protean career orientation with individual objects that are still in preparation to enter the workplace (i.e., students), and 3) this finding can be a reference for higher education institution to facilitate students career planning early.